Flow as a Key Predictor of Subjective Well-Being Among Chinese University Students: A Chain Mediating Model - Wu, Jun; Xie, Mei; Lai, Yao; Mao, Yanhui; Harmat, Laszlo (Frontiers in Psychology, 2021)
The present study investigated a conceptual model by testing university students’ flow experience and subjective well-being during COVID-19 via considering their underlying mechanisms of academic self-efficacy and self-esteem. A total of 1109 Chinese university students completed a questionnaire containing scales of Subjective Well-being, Flow, Academic Self-efficacy and Self-esteem. Results yielded from the structural equation modelling analysis indicated a significant and positive association between flow experience and subjective well-being, and such an association was sequentially mediated by academic self-efficacy and self-esteem. Findings also provided empirical evidence for the proposed model highlighting the significant role of flow experience at the higher educational context in predicting Chinese university students’ subjective well-being, and how such a relation can be supported by suggested mediating roles academic self-efficacy and self-esteem played.